CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY OF LANGHIAN DEPOSITS IN LEFKAS (IONIAN ISLANDS) - Triantaphyllou, M. V (Bulletin of the Geological Society of Greece, 2010)
Spanochorion composite section (NE Lefkas) and Aghios Vassilios section (W Lefkas) have been studied semiquantitatively for their calcareous nannofossil content. The calcareous nannofossil biostratigraphy, performed at the Paxos unit atypical flysch sediments of Aghios Vassilios section, permits their biostratigraphic correlation with the uppermost part of NN4 biozone and the lower part of NN5 biozones (Martini, 1971) or MNN4b and MNN5a (Fornaciari and Rio, 1996), which chronostratigraphically point to Early Langhian age and range between 15.974 and 14.53 Ma. Τhe most interesting biostratigraphic result is the detection of the Sphenolithus heteromorphus Paracme End at the base of Aghios Vassilios section, a biohorizon that marks the basal Langhian deposits in the Mediterranean region. The mollasic sediments of Spanochorion section are more or less of the same age, ranging between 15.5 and 14.53 Ma. The biostratigraphic results of the present study reinforce the hypothesis that the molassic sediments of NE Lefkas Island behind the Ionian thrust were isochronously deposited with Paxos atypical flysch sequences deposited in front of Ionian thrust, at least until Early Langhian times.